Line H (Spain) - Baselga M. (Rabbit genetic resources in Mediterranean countries, 2002)
A description of the Spanish line H, developed in Valencia (Spain) is carried out. Items that are dealt with are: (i) a general description; (ii) climate and main features of its farming; (iii) performances; and (iv) genetic improvement.